Martin Luther and the Arts - Loewe, Andreas, author.
1 online resource
Keywords: Martin Luther was the architect and engineer of the Protestant Reformation, which transformed Germany five hundred years ago. In Martin Luther and the Arts , Andreas Loewe and Katherine Firth elucidate Luther’s theory and practice, demonstrating the breadth, flexibility and rigour of Luther’s use of the arts to reach audiences and convince them of his Reformation message using a range of strategies, including music, images and drama alongside sermons, polemical tracts, and his new translation of the Bible into German. Extensively based on German and English sources, including often neglected aspects of Luther’s own writings, Loewe and Firth offer a valuable survey for theologians, historians, art historians, musicologists and literary studies scholars interested in interdisciplinary comparisons of Luther’s work across the arts.